2015
DOI: 10.1039/c5cp04765j
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and topological determinants of a phosphorylation-induced disorder-to-order protein conformational switch

Abstract: We show that the phosphorylation of 4E-BP2 acts as a triggering event to shape its folding-function landscape that is delicately balanced between conflicting favorable energetics and intrinsically unfavorable topological connectivity. We further provide first evidence that the fitness landscapes of proteins at the threshold of disorder can differ considerably from ordered domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
(36 reference statements)
2
18
2
Order By: Relevance
“…It should also be possible to capture the effect of DNA, RNA or even ligand binding on the conformational landscapes of larger proteins by extending a recently developed protocol that maps the protein-ligand interactions on to the protein ( Munshi et al., 2018b ). Similarly, post-translational modifications, particularly those that introduce or remove charges can be introduced in a straightforward manner as before ( Gopi et al., 2015 ). The bWSME model thus stands on the cusp of addressing and exploring numerous questions on the conformational behavior of large proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be possible to capture the effect of DNA, RNA or even ligand binding on the conformational landscapes of larger proteins by extending a recently developed protocol that maps the protein-ligand interactions on to the protein ( Munshi et al., 2018b ). Similarly, post-translational modifications, particularly those that introduce or remove charges can be introduced in a straightforward manner as before ( Gopi et al., 2015 ). The bWSME model thus stands on the cusp of addressing and exploring numerous questions on the conformational behavior of large proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The Wako-Saitô-Muñoz-Eaton (WSME) model is one such statistical mechanical model that was first developed by Wako and Saitô ( Wako and Saito, 1978a , Wako and Saito, 1978b ), discussed in detail by Gō and Abe ( Go and Abe, 1981 , Abe and Go, 1981 ), and then later independently developed by Muñoz and Eaton (1999) . Originally seen as a physical tool to predict the folding rates of proteins from three-dimensional structures ( Muñoz and Eaton, 1999 , Henry and Eaton, 2004 ), the model has expanded its scope to quantitatively analyze folding behaviors of folded globular domains ( Bruscolini and Naganathan, 2011 , Garcia-Mira et al., 2002 , Narayan and Naganathan, 2014 , Narayan and Naganathan, 2017 , Narayan and Naganathan, 2018 , Naganathan and Muñoz, 2014 , Naganathan et al., 2015 , Munshi and Naganathan, 2015 , Rajasekaran et al., 2016 , Narayan et al., 2017 , Itoh and Sasai, 2006 ), repeat proteins ( Faccin et al., 2011 , Sivanandan and Naganathan, 2013 , Hutton et al., 2015 ), disordered proteins (with appropriate controls) ( Naganathan and Orozco, 2013 , Gopi et al., 2015 , Munshi et al., 2018a ), predict and engineer thermodynamic stabilities of proteins via mutations ( Naganathan, 2012 , Naganathan, 2013b , Rajasekaran et al., 2017 ) and entropic effects ( Rajasekaran et al., 2016 ), model allosteric transitions ( Itoh and Sasai, 2011 , Sasai et al., 2016 ), protein-DNA binding ( Munshi et al., 2018b ), quantifying folding pathways at different levels of resolution ( Henry et al., 2013 , Kubelka et al., 2008 , Gopi et al., 2017 ), force-spectroscopic measurements ( Imparato et al., 2007 ) and even crowding effects ( Caraglio and Pelizzola, 2012 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…We also chose a state without any terminal helix and with both β1 and the long loop detached from the other three β-strands (3β) because it was frequently observed as a metastable intermediate during high-temperature unfolding and was also proposed as an important folding intermediate in a previous computational study. 29 Finally, we extracted a representative unfolded state (U) at 480 K. A clustering analysis based on the Cα RMSD of residues 37–46 was conducted for the trajectories after unfolding. From the most populated cluster, the structure with the lowest backbone RMSD to the folded state was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Several computational studies have been conducted to study the folding mechanism of this system and the origin of stabilization by phosphorylation. Gopi et al 29 studied different phosphorylated states using the statistical mechanical Wako–Saitô–Muñoz–Eaton (WSME) model. 30 , 31 They found that phosphorylation-induced stabilization in this system originated from strong electrostatic interactions between phosphate groups and nearby Arg residues, as generally observed in other systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation